Mothers’ personality and children with feeding and eating disorders: a nested case–control study - Aml Al Marzouki Al Agroudi; Ibrahem Hamdey Rashed; Sohier Yahia; Salwa Tobar (Middle East Current Psychiatry, 2023)
Abstract Background Feeding and eating disorders are major factors in nutrition problems. Mothers have a big role in shaping feeding and eating behaviors. This study aimed at estimating the prevalence of feeding and eating disorders among children in pediatric outpatient clinics (6–12 years old) and comparing personality factors among mothers of children with feeding and eating disorders versus those without feeding and eating disorders. Results This study included 528 children who were screened for feeding and eating disorders using the DSM-5. For the detected children, their mothers’ personalities were assessed using Cattell’s 16 personality factor test after history was taken using a child psychiatric sheet. The resulting prevalence of feeding and eating disorders is 13%, and the major mother’s personality factor that contributed is the control factor. Conclusions Certain personality factors of the studied mothers (controlled, tender-minded, imaginative, forthright, and apprehensive) correlate with the prevalence of feeding and eating disorders among their children, compared with those without feeding and eating disorders. Mothers’ personalities should be assessed in children with feeding and eating disorders, especially when these factors seem likely.